(untitled) (Herald of Journalism, 2019)
The article examines the work of the poet, religious leader Almagambet Ospanuly, who supported the idea of Alash, and after the revolution actively participated in the work of public education. The purpose of this work: to show the work of the young Kazakh intelligentsia of the early 20th century on the awakening of the national identity of the nation. Tasks: familiarization of the poet’s works published in the Alash press. The object of the research is the publication of the journal «Aikap» and the newspaper «Kazakh». The basis of the study is the achievement of understanding the spread of the idea of Alash among the masses. It is said that the reforms of the early twentieth century in the Russian Empire had a positive effect on raising the political consciousness of the Kazakh people.Kazakh youth, educated in the cities of St. Petersburg, Moscow, Kazan and Ufa, Troitsk, took an active part in educating the people and rais-ing the cultural level of the population. And also they laid the foundation of the first Kazakh press. The first Kazakh magazine «Aikap» was published in 1911-1915 in the city of Troitsk, its chief editor was the poet-educator Mukhamedzhan Seralin. A newspaper «Kazakh» was published in the years 1913-1918 in the city of Orenburg. Its editor was the founder of Kazakh linguistics Ahmet Baitursynov. The poet-educator, religious figure from Turgay Almagambet Ospanuly took an active part in the work of these two publications. Creativity of the poet was studied only recently by a narrow circle of scientists, which explains the small number of bibliographies on this topic.